The Effect of Reading to Learn (R2L) Based Modules on Increasing Stedents HOTs-Literacy In Chemical Bonding Materials - Putra, Adhitya Shahrian; Siahaan, Stephani Yunita; Aulia, Shelly; Khairunisa, Dira; Juwita, Intan; Batubara, Diva Angelica Amanda; Zubir, Moondra (Universitas Lampung, 2024)
This study aims to identify whether the use of Reading to Learn (R2L) based modules can affect the improvement of students' HOTs-Science Literacy in chemical bonding material. The population in this study consisted of students of class XI MAN 1 MEDAN who were divided into six classes. The sample of the study was 30 students of class XI MIPA 1. The instrument used in this study was a test with 15 multiple-choice questions. Hypothesis testing was carried out using a regression model, with the results of the study showing a sig value of 0.01 <? (0.05), which means Ha is accepted and H0 is rejected. This shows that the use of R2L based modules has an effect on students' HOTs-Science Literacy abilities. Furthermore, in science literacy abilities, a sig value of 0.03 <? (0.05) was obtained, which also shows that Ha is accepted and H0 is rejected, indicating the influence of science literacy abilities on improving students' HOTs-Science Literacy in chemical bonding material. Finally, the influence of the R2L-based module on students' HOTs-Science Literacy abilities in solving HOTs-Literacy problems on chemical bonding material simultaneously shows a sig value of 0.00 < ? (0.05), which means that the R2L-based module has a significant influence on students' HOTs-Science Literacy abilities on the material.Keywords: Reading To Learn (R2L) Based Module, HOTs-literacy, Chemical BondsDOI: 10.23960/jppk.v13i3.31940